Review Cerebral Ischemic Tolerance and Preconditioning: Methods, Mechanisms, Clinical Applications, and Challenges - Hao, Yulei; Xin, Meiying; Feng, Liangshu; Wang, Xinyu; Wang, Xu; Ma, Di; Feng, Jiachun (Frontiers in Neurology, 2020)
Stroke is one of the leading causes of morbidity and mortality worldwide, and it is increasing in prevalence. The limited therapeutic window and potential severe side effects prevent the widespread clinical application of the venous injection of thrombolytic tissue plasminogen activator and thrombectomy, which are regarded as the only approved treatments for acute ischemic stroke. Triggered by various types of mild stressors or stimuli, ischemic preconditioning (IPreC) induces adaptive endogenous tolerance to ischemia/reperfusion (I/R) injury by activating a multitude cascade of biomolecules, for example, proteins, enzymes, receptors, transcription factors, and others, which eventually lead to transcriptional regulation and epigenetic and genomic reprogramming. During the past 30 years, IPreC has been widely studied to confirm its neuroprotection against subsequent I/R injury, mainly including local ischemic preconditioning (LIPreC), remote ischemic preconditioning (RIPreC), and cross preconditioning. Although LIPreC has a strong neuroprotective effect, the clinical application of IPreC for subsequent cerebral ischemia is difficult. There are two main reasons for the above result: Cerebral ischemia is unpredictable, and LIPreC is also capable of inducing unexpected injury with only minor differences to durations or intensity. RIPreC and pharmacological preconditioning, an easy-to-use and non-invasive therapy, can be performed in a variety of clinical settings and appear to be more suitable for the clinical management of ischemic stroke. Hoping to advance our understanding of IPreC, this review mainly focuses on recent advances in IPreC in stroke management, its challenges, and the potential study directions.